2011
DOI: 10.1111/j.1467-8535.2009.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles and student perceptions of the use of interactive online tutorials

Abstract: This study examined the effects of learning styles on learner perceptions of the use of interactive online tutorials. Learners were categorised into five learning style categories and four learning modalities. The responses to a questionnaire with four survey dimensions were analysed in order to ascertain differences based on learning styles, gender and class standing. Researchers investigated whether relationships, interactions, main effects and associations between the variables and survey dimensions existed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In the few studies that have been conducted, results are inconsistent, further implicating a need for additional study (Chyung, 2007). For example, a study conducted by Bolliger and Supanakorn (2011) found that females prefer more multimodal learning, whereas males prefer more unimodal learning. These findings directly contrast those of Wehrwein, Lujan, and Dicarlo (2007), who reported females prefer unimodal learning and males prefer multimodal learning.…”
Section: Gendermentioning
confidence: 99%
“…In the few studies that have been conducted, results are inconsistent, further implicating a need for additional study (Chyung, 2007). For example, a study conducted by Bolliger and Supanakorn (2011) found that females prefer more multimodal learning, whereas males prefer more unimodal learning. These findings directly contrast those of Wehrwein, Lujan, and Dicarlo (2007), who reported females prefer unimodal learning and males prefer multimodal learning.…”
Section: Gendermentioning
confidence: 99%
“…5 Creating an online set of lessons would address three issues: 1) supplement one-shot library instruction events, 2) provide an opportunity for instruction even when a librarian is not embedded in a course, and 3) showcase the library on campus as a key player in supporting the growing focus on online instruction. 6 By reviewing the literature, the library team realized that more interactive online lessons needed to be developed in order to keep students' attention and to increase learning retention. The team incorporated the guidance found in the published research on MOOCs, as well as the methods that consisted of good online instruction.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted by Bolliger and Supanakorn (2011) revealed that the majority of the study participants thought the tutorials were useful in learning and reviewing the material. The majority of the participants thought the tutorials helped them spend less time in learning the material and completing the assignment.…”
Section: Student Perception Of Web-based Tutorialsmentioning
confidence: 96%